ASSOCIATION OF LIVER FATTY ACID BINDING PROTEIN WITH ACUTE KIDNEY INJURY IN PAEDIATRIC PATIENTS AFTER CARDIAC SURGERY - Basharat Khan, Muhammad; Naseem, Tahira; wazir, Haseen dil; Ayyub, Aisha; bin saad, Ammar; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acute kidney injury (AKI) is a common complication after cardiac surgery. Like Creatinine level, the role of L-FABP in renal injury and its recovery had been shown by studies, so by using/measuring urinary Liver fatty acid-binding protein (uL-FABP) levels it can be a valuable biomarker for monitoring and diagnosis of various renal diseases. The study aimed to determine L-FABP as a biomarker for early diagnosis of AKI acute kidney injury in paediatric patients after cardiac surgery so that early treatment interventions can prevent AKI morbidity. Methods: This descriptive study was conducted in the Pathology laboratory of Sheikh Zayed Hospital, Lahore from 2015 to 2016. Selected through convenience sampling, patients' blood and urine were analysed for desired markers. Results: Out of 88, 10 (11.4%) patients developed AKI after cardiac surgery. In patients with AKI, serum creatinine levels started to rise at 24-48 h after surgery whereas uL-FABP was to be high at 4h. The optimal cut-off value of uLFABP was found 269 ng/l, with this cut-off value sensitivity of marker at four hours to recognize AKI was found to be 80% and specificity was 83.3%, the positive and negative predictive values were 38.1% and 97.0% respectively with an accuracy level 83.0%. Conclusion: It may be concluded from this study that uL-FABP may be considered as an early predictor of the development of AKI in paediatric patients undergoing cardiac surgery.